An ergonomic intervention : the effect of a chair and computer screen height adjustment on musculoskeletal pain and sitting comfort in office workers - Van Vledder, Nicole (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScPhysio)--Stellenbosch University, 2015.